Bacterial l‐asparaginases for cancer therapy: Current knowledge and future perspectives. Issue 11 (16th April 2019) - Ghasemian, Abdolmajid; Al‐marzoqi, Ali‐Hussein; Al‐abodi, Hiba Riyadh; Alghanimi, Yasemin Khudiar; Kadhum, Samah Ahmed; Shokouhi Mostafavi, Seyyed Khalil; Fattahi, Azam
Abstract: l ‐Asparaginases hydrolyzing plasma l ‐asparagine and l ‐glutamine has attracted tremendous attention in recent years owing to remarkable anticancer properties. This enzyme is efficiently used for acute lymphoblastic leukemia (ALL) and lymphosarcoma and emerged against ALL in children, neoplasia, and some other malignancies. Cancer cells reduce the expression of l ‐asparaginase leading to their elimination. The l ‐asparaginase anticancerous application approach has made incredible breakthrough in the field of modern oncology through depletion of plasma l ‐asparagine to inhibit the cancer cells growth; particularly among children. High level of l ‐asparaginase enzyme production by Escherichia coli, Erwinia species, Streptomyces, and Bacillus subtilis species is highly desirable as bacterial alternative enzyme sources for anticancer therapy. Thermal or harsh conditions stability of those from the two latter bacterial species is considerable. Some enzymes from marine bacteria have conferred stability in adverse conditions being more advantageous in cancer therapy. Several side effects exerted by l ‐asparaginases such as hypersensitivity should be hindered or decreased through alternative therapies or use of immune‐suppressor drugs. The l ‐asparaginase from Erwinia species has displayed remarkable traits in children with this regard. Noticeably, Erwinia chrysanthemi l ‐asparaginase exhibited negligible glutaminase activity representing a promising efficiency mitigating related side effects. Application of software such as RSM would optimize conditions for higher levels of enzyme production. Additionally, genetic recombination of the encoding gene would indisputably help improving enzyme traits. Furthermore, the possibility of anticancer combination therapy using two or more l ‐asparaginases from various sources is plausible in future studies to achieve better therapeutic outcomes with lower side effects.